2015
DOI: 10.1002/cam4.566
|View full text |Cite
|
Sign up to set email alerts
|

Distal bile duct carcinomas and pancreatic ductal adenocarcinomas: postulating a common tumor entity

Abstract: The set definition of distal cholangiocarcinomas and adenocarcinomas of the pancreatic head is challenged by their close anatomical relation, similar growth pattern, and corresponding therapeutic outcome. They show a mutual development during embryologic organ formation and share phenotypic characteristics. This review will highlight the similarities with regard to the common origin of their primary organs, histopathological similarities, and modern clinical management. Thus, we propose to subsume those entiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 94 publications
0
27
0
Order By: Relevance
“…Their data from a human cancer-profiling array shows that the apelin gene is expressed in a variety of benign and malignant tissues, however, the frequency of gene up regulation was high in carcinomas of the colon, skin and pancreas [11]. They did not see an increase of apelin gene expression in tumors of liver origin, however, carcinomas of the pancreatic head and extrahepatic CCA share similar features, including embryologic origin and several phenotypic characteristics [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Their data from a human cancer-profiling array shows that the apelin gene is expressed in a variety of benign and malignant tissues, however, the frequency of gene up regulation was high in carcinomas of the colon, skin and pancreas [11]. They did not see an increase of apelin gene expression in tumors of liver origin, however, carcinomas of the pancreatic head and extrahepatic CCA share similar features, including embryologic origin and several phenotypic characteristics [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Although MUC4 is undetectable in normal bile duct cells, its expression is detectable in the larger bile ducts of intra- and extrahepatic cholangiocarcinomas, as well as ductal adenocarcinomas of the pancreas [88]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim et al [44] demonstrated that plasma THBS2 is a promising diagnostic biomarker for pancreatic cancer. Given the biological similarities of dCCA and pancreatic cancer [45], further evaluation of THBS2 as a potential diagnostic biomarker of dCCA should be encouraged. We have not found any previous study in which the expression of THBS2 in paired lymph node metastases was investigated.…”
Section: Discussionmentioning
confidence: 99%